1992
DOI: 10.7863/jum.1992.11.3.95
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial Doppler ultrasonography: diagnostic criteria

Abstract: Fifty-one patients (86 legs) were studied from the aorta to the popliteal artery with both duplex ultrasonography and arteriography with the intention of establishing diagnostic ultrasonographic criteria for degrees of stenosis >50% and determining the effect of multisegment disease on the accuracy of these criteria. Receiver operator characteristic curves were used to determine diagnostic criteria for >50%, >70%, >90% diameter stenoses or occlusions. A stenosis of >70% was diagnosed either if the peak systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 7 publications
0
35
0
Order By: Relevance
“…Peak systolic velocity in lower limb vessel segments was measured to determine the grade of stenosis as previously described. 16 In 111 patients with femoral disease (50 on placebo and 61 on ramipril), we also determined volume flow. Femoral disease was classified as ≥50% stenosis but no occlusion in the common or superficial femoral arteries.…”
Section: Duplex Ultrasonographymentioning
confidence: 99%
“…Peak systolic velocity in lower limb vessel segments was measured to determine the grade of stenosis as previously described. 16 In 111 patients with femoral disease (50 on placebo and 61 on ramipril), we also determined volume flow. Femoral disease was classified as ≥50% stenosis but no occlusion in the common or superficial femoral arteries.…”
Section: Duplex Ultrasonographymentioning
confidence: 99%
“…Occlusion was present most commonly in posterior tibial arteries (30.77%), followed by anterior tibial artery (20%) and peroneal artery (13.1%). In the study by Sacks et al sixteen of 86 (19%) legs had no occlusion, whereas seventy of 86 (81%) legs had occluded segment in vessel [14].…”
Section: Computed Tomography (Ct) Angiography Findingsmentioning
confidence: 99%
“…The mean peak systolic was highest for common femoral artery (90.99 ± 28.6 cm/s) and lowest for dorsalis pedis artery (58.44 ± 39.59 cm/s). Sacks et al in their study observed the gradual decrease in peak systolic velocity from iliac to popliteal artery [14]. Resistance Index (RI) is a quantitative analysis of the waveform and reflects resistance to blood flow.…”
Section: Ultrasound Color Doppler Findingsmentioning
confidence: 99%
“…For patients who do not develop specific limb or cardiovascular symptoms, exercise may be terminated when patients achieve a high functional peak systolic velocity ratios have been found to be the most accurate diagnostic criterion. A ratio greater than 2 is commonly used to diagnose a stenosis greater than 50% diameter (201,202,205,207), although other ratios have been used (203,204,206,210). Some studies have attempted to further calibrate the duplex technique to distinguish between degrees of stenosis between 50% and 75% versus 75% and 99% (203,204,207,210).…”
Section: Treadmill Exercisementioning
confidence: 99%
“…Duplex ultrasound also has broad clinical utility for evaluation of aneurysms, arterial dissection, popliteal artery entrapment syndrome, evaluation of lymphoceles, and assessment of soft tissue masses in individuals with vascular disease. Although duplex ultrasound includes images, either in black and white or color format, the primary clinically relevant information derived from duplex studies has been validated from analysis of the velocity of blood flow (201)(202)(203)(204)(205)(206)(207)(208)(209). Quantitative criteria used to diagnose stenoses are based on peak systolic velocity and peak systolic velocity ratios within or beyond the stenosis compared with the adjacent upstream segment, the presence or absence of turbulence, and preservation of pulsatility.…”
Section: Treadmill Exercisementioning
confidence: 99%